MOS Transistor Mask Design Using SEM Based E-Beam Lithography - Uda, Hashim, Prof. Dr.; Nur Hamidah, Abdul Halim; Mohammad Nuzaihan, Md Nor; Zul Azhar, Zahid Jamal, Prof. Dr. (Malaysian Invention & Design Society (MINDS), 2010)
Prof. Dr. Uda Hashim and his team won silver for MOS Transistor Mask Design Using SEM Based E-Beam Lithography at ITEX 2006, 19th - 21st May 2006 at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.